PENDIDIKAN AGAMA KRISTEN DI TAMAN EDEN - Urbanus Sukri (Inculco Journal of Christian Education, 2021)
Humans are "homo educandum", that is, learning creatures. This is the trigger for the emergence of educational activities in human life. Education is intentional and planned learning. In minimum education there are elements of teachers, students, learning materials, learning strategies, and learning media. Education begins when there is social interaction between humans. Since humans were placed in the garden of Eden, humans have started to learn. Learn about everything. Especially learning about life interacting with the surrounding environment and God.In Eden Gardens there are theological (spiritual) learning activities. In the Garden of Eden, Adam learned primarily about the relationship with his creator. This is a theological relationship. Theological or spiritual learning in the context of contemporary Christianity is referred to as Christian Religious Education. The main purpose of education (learning activities) is to acquire theological or spiritual knowledge.The research in this paper is qualitative-descriptive. The author tries to interpret the existing text. The result is a theological finding about the concept of spiritual education (Christian Education) in the garden of Eden.    Abstrak :Manusia adalah “ homo educandum”, yaitu makhluk pembelajar. Ini adalah pemicu munculnya kegiatan pendidikan dalam kehidupan manusia. Pendidikan adalah pembelajaran yang disengaja dan terencana. Didalam pendidikan minimal ada unsur guru, murid, materi pembelajaran, strategi pembelajaran, dan media pembelajaras. Pendidikan dimulai ketika ada interaksi sosial diantara manusia. Sejak manusia ditempatkan ditaman Eden, manusia sudah mulai belajar. Belajar tentang segala sesuatu. Terutama belajar tentang hidup berinteraksi dengan lingkungan sekitar dan Allah.Ditaman Eden ada kegiatan pembelajaran teologis (spiritual). Ditaman Eden, Adam belajar terutama tentang hubungan dengan sang penciptanya. Ini adalah hubungan secara teologis. Pembelajaran teologis atau rohani dalam konteks kekristenan masa kini disebut dengan istilah Pendidikan Agama Kristen. Tujuan utama pendidikan (kegiatan pembelajaran) tersebut adalah untuk memperoleh pengetahuan teologis atau kerohanian.Penelitian dalam tulisan ini bersifat kualitatif-deskriptif. Penulis mencoba menafsirkan teks yang ada. Hasilnya adalah temuan teologis tentang konsep pendidikan rohani (Pendidikan Agama Kristen) ditaman Eden.